AUTISM SPECTRUM DISORDER AND SOCIAL VULNERABILITY IN BRAZIL: A CRITICAL ANALYSIS OF SUPPORTIVE PUBLIC POLICIES (REMUNOM, 2025)
Autism Spectrum Disorder (ASD) imposes significant socioeconomic challenges on families in Brazil, who face barriers in accessing fundamental rights. Despite a protective legal framework, such as Law No. 12,764/2012, the effectiveness of public policies is compromised by bureaucratic obstacles and exclusionary criteria, transferring the burden of care to the family unit. This article aims to analyze the social and economic impacts associated with ASD, with an emphasis on the barriers faced by families, treatment costs, and the effectiveness of Brazilian public policies. The methodology employed consists of a qualitative literature review. The results indicate that access to the Continuous Cash Benefit (BPC) is hindered by restrictive income criteria that disregard the high costs of multiprofessional treatments. In education, the absence of school support professionals in the public system forces the hiring of private caregivers, deepening financial vulnerability. It is concluded that the discrepancy between legislation and practical reality perpetuates a cycle of inequality, financially burdening families and limiting the full development of individuals with ASD. There is an urgent need to reformulate the criteria for accessing benefits, guarantee specialized educational support, and create direct support policies for caregivers to ensure the dignity and social inclusion of this population.